World development report 2007 : development and the next generation - The World Bank; Jimenez, Emmanuel; World Bank (Washington DC : World Bank, 2007)
The theme of The World Development Report 2007 is youth - young people between the ages of 12 to 24. As this population group seeks identity and independence, they make decisions that affect not only their own well-being, but that of others, and they do this in a rapidly changing demographic and socio-economic environment. Supporting young people$1 (Bs transition to adulthood poses important opportunities and risky challenges for development policy. Are education systems preparing young people to cope with the demands of changing economies? What kind of support do they get as they enter the labor market? Can they move freely to where the jobs are? What can be done to help them avoid serious consequences of risky behavior, such as death from HIV-AIDS and drug abuse? Can their creative energy be directed productively to support development thinking? The report will focus on crucial capabilities and transitions in a young person$1 (Bs life: learning for life and work, staying healthy, working, forming families, and exercising citizenship. For each, there are opportunities and risks; for all, policies and institutions matter. s
"This report has been prepared by a core team led by Emmanuel Y. Jimenez and comprising Jean Fares ... [et al.]." -- p. xiii.
Includes index.
osa; 13/07/16
Ref.
Keywords: Economic development; Youth in development; Youth, Social conditions; Youth, Economic conditions; Youth, Health and hygiene; Youth, Government policy; Youth, Services for; Developing countries